Kecenderungan Peningkatan Piutang Pajak Kendaraan Bermotor Di Pusat Pengelolaan Pendapatan Daerah Wilayah Kota Bandung Iii - Mubarok Mubarok; Jaliludin Muslim; Luthfi Diartama (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2019)
The Sources of state revenue derived from motor vehicle tax in the Regional Management Center of the City of Bandung show a significant downward trend every year. This study aims to analyze the receivables of East Bandung taxpayers to the Regional Revenue Management Center and the settlement mechanism so that the existing receivables can be minimized and can be resolved. This study uses a qualitative approach to the type of descriptive research. In order to collect research data, researchers used interview techniques and literature studies. The results of this study explain that the mismatch of the target and the realization of motor vehicle tax tends to reduce state revenue in the tax sector, the factors causing it are the lack of awareness of taxpayers in East Bandung and Bandung City Region III, the lack of socialization for people who have receivables, and inadequate human resources tax apparatus both quantitatively and qualitatively.